2020
DOI: 10.1002/ece3.5979
|View full text |Cite
|
Sign up to set email alerts
|

Postintroduction evolution contributes to the successful invasion of Chromolaena odorata

Abstract: The evolution of increased competitive ability (EICA) hypothesis states that, when introduced in a novel habitat, invasive species may reallocate resources from costly quantitative defense mechanisms against enemies to dispersal and reproduction; meanwhile, the refinement of EICA suggests that concentrations of toxins used for qualitative defense against generalist herbivores may increase. Previous studies considered that only few genotypes were introduced to the new range, whereas most studies to test the EIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…2019; Li et al. 2020). Despite the fact that most invasive species engage in mutualism, we know little about how invasion affects the evolution of positive species interactions (Richardson et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Li et al. 2020). Despite the fact that most invasive species engage in mutualism, we know little about how invasion affects the evolution of positive species interactions (Richardson et al.…”
mentioning
confidence: 99%
“…Our study assesses the net effect of many stages of biological invasion on symbiotic interactions, integrating the evolutionary changes that can occur throughout the invasion process (Zenni et al 2017). Our approach does not determine whether differences between invaded-and native-range symbioses are due to effects of initial colonization (Brown et al 2014) or due to subsequent years of evolution in separate ranges (Li et al 2020). Genomics and historical records suggest that M. polymorpha and E. medicae were cointroduced to North America from the Mediterranean in the 1700s (Wing 1912;Porter et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher amounts of odoratin in non-native ranges provide greater competitive advantages (Zheng et al, 2015) Acutellerin-4 0 ,6,7-trimethy ether, 4 0 ,5,6,7tetramethoxyflavone, isosakuranetin, 3,5-dihydroxy-7,4 0 -dimethoxyflavone, dihydrokaempferol-3-methoxy ether, and kaempferide-4 0 -methoxy ether Greater amounts of flavonoids in the non-native range provide competitive advantages and better defence against soilborne pathogens (Li et al, 2020) Root leachates Root leachates of C. odorata can drive accumulation of native soil pathogens (Mangla et al, 2008) Centaurea diffusa (native to Europe; invasive in North America)…”
Section: Odoratinmentioning
confidence: 99%
“…In another study, Li et al . (2020) found that invasive populations of C . odorata produced greater quantities of phenolic compounds; some of these phenolic compounds confer stronger defence and others may suppress native species (Table 1).…”
Section: Novel Chemicals Introduced By Nismentioning
confidence: 99%